The Influence of Learning Style on Students' English Learning Outcomes: Pengaruh Gaya Belajar Terhadap Hasil Belajar Bahasa Inggris Siswa - Rosanti, Tania Eva; Astuti, Ruli (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study was to analyze the various student learning styles and influence of the learning styles on English learning outcomes of fourth grade students at MI Darul Hidayah Sudimoro. This study uses quantitative methodes and data collection techniques using instruments in the form questionaire. Sample in this study were fourth grade student at MI Daruk Hidayah Sudimoro totaling 32 students. The data form the questionaire showed that the learning styles of fourth grade student in english subject at MI Darul Hidayah Sudimoro were 17 students (53%) visual learning style, 11 students (34.5) had an auditory learning style, and 4 students (12.5%) have a kinesthetic learning style. Learning style have a positive and significant impact on the learning outcomes of fourth grade students in english grade subject at MI Darul Hidayah Sudimoro. It can be seen frm the results of the regression test where the regression coefficient of the learning style variable is 0.293. the higher the value of the learning variable, the higher value of the student learning otcomes variable